THE PERSPECTIVE OF TECHNOLOGY ACCEPTANCE MODEL (TAM) APPROACH IN IMPLEMENTATION OF E-LEARNING IN AMWAY INDONESIA - Burhanudin, Aep; Bari, Abdul (Indikator: Jurnal Ilmiah Manajemen dan Bisnis, 2019)
Abstract. In implementing an information system in an institution, it is necessary to consider user acceptance of the information system. The application of information systems can be said to fail if the user turns out to be unable to accept or is unwilling to use the information system. As an company organization, Amway Indonesia also implements an e-learning system to support the teaching and learning process of its distributors. Mandatory users of e-learning are members and all of the distributors. Since the system was implemented, there has never been an evaluation of user acceptance of this e-learning system. This research was conducted to test the user acceptance of e-learning by using the Technology Acceptance Model (TAM). Testing is done by measuring the influence between variables in the TAM model which includes variables Perceived Ease of Use, Perceived Usefulness, Attitude Toward Using, Behavioral Intention and Actual Usage. The statistical testing method that is carried out is the statistical test of validity, reliability, normality, and testing the effect of factors using SPSS.Â  Evaluation data obtained through questionnaires distributed to respondents (Amway member distributors). One of the six hypotheses proposed one hypothesis was declared not accepted, namely the hypothesis that states Perceived Usefulness affect Behavioral Intention. The other five hypotheses namely Perceived Ease of Use has an effect on Perceived Usefulness, Perceived Usefulness affects Attitude Toward Using, Perceived Ease of Use has an effect on Attitude Toward Using, Attitude Toward Using has an effect on Behavioral Intention, Behavioral Intention has an effect on Actual Usage declared acceptable.